Pornografi Internet dan Perilaku Seksual Pranikah Pada Remaja: Literature Review - Fransiska Imavike Fevriasanty (Perhimpunan Dokter Kedokteran Komunitas dan Kesehatan Masyarakat Indonesia (PDK3MI), 2020)
Introduction: The digital era of information requires teenagers to find information via the internet where easy internet access is not without risks. Coupled with a great sense of curiosity in teenagers, it will encourage them to open pornographic sites when they are overwhelmed by feelings of loneliness and boredom with complicated conditions in the family or incompatibility in friendship. Aim of study: This article aims to discuss the antecedents of internet pornography behavior and premarital sexual behavior among adolescents. Method: The research method is to use literature study techniques on 25 articles from the Google Scholar and Proquest databases. Results and Discussion: The literature study shows that addiction to internet pornography can lead to deviant behavior such as premarital sexual behavior. Premarital sexual behavior in adolescents can occur when adolescents want to try what they see on pornographic sites to be practiced on their friends of the opposite sex or to their partners. The situation in which premarital sexual behavior is a trend among adolescents will ultimately create social disease in the society which has an impact on the mental damage of the nation's future generations. Conclusion: The conclusion from this literature study is that premarital sexual behavior in adolescents will increase the incidence of sexually transmitted diseases such as HIV / AIDS. So it is hoped that health workers, the community, and related parties will get the same understanding considering that adolescents are very vulnerable to the negative influence of the internet without neglecting its positive effects on adolescent psychosocial development and academic achievement.